Sick bunnies and pocket dumps: "Not-selfies" and the genre of self-representation. (3rd April 2017) - Tiidenberg, Katrin; Whelan, Andrew
ABSTRACT: This article develops and troubles existing approaches to visual self-representation in social media, questioning the naturalized roles of faces and bodies in mediated self-representation. We argue that self-representation in digital communication should not be treated as synonymous with selfies, and that selfies themselves should not be reductively equated with performances of embodiment. We do this through discussing "not-selfies": visual self-representation consisting of images that do not feature the likenesses of the people who share them, but instead show objects, animals, fictional characters, or other things, as in the practices of #EDC ("everyday carry") and #GPOY ("gratuitous picture of yourself") on platforms such as Tumblr, Facebook, Instagram, and reddit. We present an account of self-representation as an emergent, recognizable, intertextual genre, and show that #EDC and #GPOY practices are best conceptualized as instances of self-representation.